Light-mediated activation of PpPSY enhances β-carotene accumulation in pear fruit peel - Zhang, Li; Du, Wei; Tu, Junfan; Zhu, Hongyan; Li, Xianming (Frontiers in Plant Science, 2025)
Light is a key environmental factor that regulates fruit development and influences several important quality traits, including pericarp color. In pear fruits, carotenoids are the primary determinant of pericarp color. However, the molecular mechanisms underlying light-mediated carotenoid accumulation remain poorly understood. This study investigated the carotenoid contents in the peels of non-bagged (light-exposed) and bagged (shaded) pear fruits (Cuiguan, Pyrus pyrifolia) and revealed a significant differences in β-carotene content between the two treatments. Transcriptome analysis revealed that the expression of phytoene synthase (PSY) was downregulated in bagged fruits, highlighting the regulatory role of PSY in carotenoid metabolism. To further validate this, we transiently overexpressed PSY, which resulted in a marked increase in β-carotene levels at the injection site. Conversely, transient silencing of PSY led to a significant reduction in the β-carotene content, confirming the pivotal role of PSY in regulating β-carotene accumulation. Promoter analysis revealed that agamous-like 8 (AGL8) directly binds to the PSY promoter to activate its transcription. Protein−protein interaction assays demonstrated that AGL8 interacts with LEAFY (LFY), thereby increasing PSY expression. In conclusion, the AGL8-LFY complex coactivates PSY expression, regulating β-carotene accumulation in pear fruit. This study provides new insights into the regulatory network governing fruit peel coloration, with potential applications for cultivation strategies to improve fruit quality.